2019
DOI: 10.1186/s40360-019-0355-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of immunological, inflammatory, and oxidative stress biomarkers in gasoline station attendants

Abstract: BackgroundGasoline is a complex mixture of saturated and unsaturated hydrocarbons, in which aromatic compounds, such as BTX (benzene, toluene, and xylene) feature as the main constituents. Simultaneous exposure to these aromatic hydrocarbons causes a significant impact on benzene toxicity. In order to detect early alterations caused in gasoline station attendants exposed to BTX compounds, immunological, inflammatory, and oxidative stress biomarkers were evaluated.MethodsA total of 66 male subjects participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Xylene and plants can be antagonists in control of oxidative processes. For example, xylene can induce oxidative stress (Niaz et al 2015;Salimi et al 2017;Moro et al 2019), while the plant extracts contain a number of antioxidants (McKay and Blumberg 2007;Giménez-Bastida et al 2017;Ban et al 2020). Another common target of xylene and plants could involve steroidogenesis: xylene suppressed it in our present and previous (see "Introduction") experiments, while the plant extracts contain a high level of phytoestrogens with physiological and therapeutical functions (Sirotkin and Harrath 2014) that can neutralize the anti-steroidogenic action of xylene.…”
Section: Can Some Plants Modify Xylene's Effects On Ovarian Functions?mentioning
confidence: 76%
“…Xylene and plants can be antagonists in control of oxidative processes. For example, xylene can induce oxidative stress (Niaz et al 2015;Salimi et al 2017;Moro et al 2019), while the plant extracts contain a number of antioxidants (McKay and Blumberg 2007;Giménez-Bastida et al 2017;Ban et al 2020). Another common target of xylene and plants could involve steroidogenesis: xylene suppressed it in our present and previous (see "Introduction") experiments, while the plant extracts contain a high level of phytoestrogens with physiological and therapeutical functions (Sirotkin and Harrath 2014) that can neutralize the anti-steroidogenic action of xylene.…”
Section: Can Some Plants Modify Xylene's Effects On Ovarian Functions?mentioning
confidence: 76%
“…This could be attributed to an increase in the activity of inflammatory agents that could have resulted in the inflammation of liver tissues. It has recently been shown that exposure to gasoline containing Tol provoked an elevation of the levels of pro-inflammatory cytokines, such as interleukin (IL)-1β, IL-6, tumor necrosis factor-α, and interferon-γ [27].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Wang et al (2012) [ 15 ] speculated that benzene-mediated hematopoietic stem cells (HSCs) toxicity involved several mechanisms of action, including CA, genomic instability, macromolecular adduct formation, oxidative stress, alteration of gene expression and epigenetic regulation, apoptosis induction, error-prone DNA repair, and disruption of tumor surveillance. Moreover, leukemia is a clonal hematological malignancy initiated by epigenetic alterations or CA, either via clastogenicity (structural CA) or aneugenicity (numerical CA) occurring in HSPCs [ 16 , 17 , 18 ]. Therefore, benzene toxicity affecting the chromosomal status of HSPCs may be one of the mechanisms of benzene-induced leukemia in humans [ 5 ].…”
Section: Introductionmentioning
confidence: 99%